PtRu nanoalloys loaded on graphene and TiO2 nanotubes co-modified Ti wire as an active and stable methanol oxidation electrocatalyst. (12th April 2018) - Han, Jingsong; Yang, Liming; Yang, Lixia; Jiang, Wenjing; Luo, Xubiao; Luo, Shenglian
Abstract: Highly active, durable and scalable fuel cell electrocatalysts are highly desirable but challenging. Herein, we first develop a novel catalyst of PtRu nanoalloys loaded on graphene modified anodic TiO2 nanotubes arrays (TNTs) grown on flexible Ti wires (denoted as PtRu/RGO/TNTs). Electrodeposited reduced graphene oxide (RGO) is used to improve the electric conductivity and facilitate the dispersion of PtRu nanoparticles. TiO2 nanotubes arrays could guarantee the large surface area, and PtRu nanoalloys are well-dispersed on the inner and external walls of the TNTs as well as the RGO surface, which could facilitate the fast mass transport and enhanced electrocatalytic activity. PtRu nanoalloys with intimate contact between the two metals is conductive to remove the harmful CO-like byproduct, resulting in superior tolerance to CO poisoning. In addition, this work first design and use the spirally flexible Ti wire electrode configuration in direct methanol fuel cell, which shows a highly efficient catalytic performance. Moreover, this kind of catalytic support is a strong candidate for other electrochemical energy conversion devices. Graphical abstract: Highlights: A soft and conductive DMFC anode with high efficiency was first fabricated. PtRu NPs and graphene were facilely electrodeposited on TiO2 nanotubes/Ti wire. The performance of PtRu alloys was much better than that of individual Pt-Ru NPs. The PtRu/RGO/TNTs shows high stability in the range from 30 °C to 70 °C.